Electrochemical device and electronic device
By providing a carbon-covered solid electrolyte first coating between the positive electrode current collector and the positive electrode material layer of the lithium-ion battery, the problem of short circuit in the lithium-ion battery during the nailing process is solved, and the nailing safety performance and low-temperature discharge performance of the battery are improved.
Patent Information
- Application Number
- CN202510034192.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-09
AI Technical Summary
During the nail-piercing process, lithium-ion batteries are prone to short-circuiting the positive electrode sheet and the negative electrode sheet, resulting in insufficient safety performance. The market urgently needs a lithium-ion battery with good safety performance in nail-piercing.
The electrochemical device design is adopted that includes a positive electrode current collector, a first coating and a positive electrode material layer. The first coating is composed of a carbon-coated solid electrolyte, a first main material and a first binder. By regulating the thickness of the first coating, the particle size distribution of the first main material and the content of the binder, a first coating with dense and good conductivity is formed.
It improves the nail-wiring safety performance of the electrochemical device, while taking into account good low-temperature discharge performance and cycling performance, enhancing the overall performance of the battery.
Smart Images

Figure CN119833558A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to an electrochemical device and an electronic device. Background Art
[0002] Electrochemical devices (such as lithium-ion batteries) have become popular in our daily lives with the development of science and technology. Lithium-ion batteries have entered our daily lives along with the advancement of science and technology and the improvement of environmental protection requirements. With the widespread popularity of lithium-ion batteries, their service life has been increasingly valued by users. Consumers, after-sales service, battery manufacturers and lithium battery manufacturers have all put forward new requirements for battery safety performance.
[0003] However, with the rapid popularization of lithium-ion batteries, the technology for their product safety is not mature. During use, the positive and negative pole pieces of lithium-ion batteries often come into contact with each other during the nailing process, or the positive and negative pole pieces are connected by nails, resulting in internal short circuits. As people pay more and more attention to the nailing safety performance of lithium-ion batteries, the market is in urgent need of a lithium-ion battery with good nailing safety performance. Summary of the invention
[0004] The purpose of the present application is to provide an electrochemical device and an electronic device, which improves the nail penetration safety performance of the electrochemical device while taking into account the cycle performance and low-temperature discharge capability of the electrochemical device.
[0005] It should be noted that in the invention content of this application, lithium-ion batteries are used as an example of electrochemical devices to explain this application, but the electrochemical devices of this application are not limited to lithium-ion batteries. The specific technical solutions are as follows:
[0006] The first aspect of the present application provides an electrochemical device, the electrochemical device includes a positive electrode plate, the positive electrode plate includes a positive electrode current collector, a first coating and a positive electrode material layer, the first coating is arranged on the surface of the positive electrode current collector, the positive electrode material layer is arranged on the surface of the first coating away from the positive electrode current collector, the first coating includes a first main material and a first binder, the first main material includes a solid electrolyte, the surface of the solid electrolyte is provided with a carbon material, the Dv50 of the first main material is 50nm to 200nm, preferably Dv50 is 100nm to 150nm. The thickness of the first coating is 0.5μm to 2μm, preferably, the thickness of the first coating is 0.5μm to 1μm. Compared with the use of non-solid electrolytes as the first coating in the prior art, the present application uses a carbon-coated solid electrolyte as the first main material in the first coating, so that the first coating has a more uniform conductive network and better conductive properties. At the same time, by adjusting the type and thickness of the first coating and the Dv50 of the first main material within the scope of this application, a first coating that is relatively dense, has high mechanical strength and good conductivity can be formed on the surface of the positive electrode current collector, thereby improving the nail penetration safety performance of the electrochemical device while taking into account good low-temperature discharge performance and cycle performance.
[0007] In one embodiment of the present application, the ratio of the thickness of the positive electrode material layer to the thickness of the first coating layer is 35 to 180. By adjusting the ratio of the thickness of the positive electrode material layer to the thickness of the first coating layer within the scope of the present application, the thickness of the positive electrode material layer and the first coating layer can be optimized to improve the nail penetration safety performance of the electrochemical device while taking into account good low-temperature discharge performance and cycle performance.
[0008] In one embodiment of the present application, the solid electrolyte includes at least one of lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide or lithium aluminum titanium phosphate. Based on the mass of the first coating, the mass percentage of the first main material is 80% to 90%. By regulating the mass percentage of the first main material and the type of solid electrolyte within the scope of the present application, the electronic conductivity of the first main material can be improved, and the transmission capacity of lithium ions and electrons can be improved, thereby improving the low-temperature discharge performance and cycle performance of the electrochemical device.
[0009] In one embodiment of the present application, the carbon material includes at least one of amorphous carbon, carbon nanotubes, conductive graphite or carbon nanofibers. Based on the mass of the first main material, the mass percentage of the carbon material is 3% to 5%. By regulating the type and mass percentage of the carbon material within the scope of the present application, a suitable carbon material can be arranged on the surface of the solid electrolyte to further improve the lithium ion and electron transport capacity of the first coating, thereby improving the low temperature discharge performance and cycle performance of the electrochemical device.
[0010] In one embodiment of the present application, the powder resistivity of the first main material is 50 Ω·cm to 100 Ω·cm. By adjusting the powder resistivity of the first main material within the scope of the present application, the first main material can have a suitable powder resistivity, improve the lithium ion and electron transport capacity of the first main material, and thus improve the low temperature discharge performance and cycle performance of the electrochemical device.
[0011] In one embodiment of the present application, the first binder includes a water-soluble metal salt compound, and the mass percentage of the first binder is 10% to 20% based on the mass of the first coating. By adjusting the mass percentage of the first binder within the scope of the present application, the first binder can interact well with the positive electrode plate, improve the interfacial adhesion, and improve the nail penetration safety performance of the electrochemical device while taking into account good low-temperature discharge performance and cycle performance.
[0012] In one embodiment of the present application, the first binder includes a water-soluble metal salt compound, and the water-soluble metal salt compound includes an alkali metal polyacrylate and / or an alkaline earth metal polyacrylate. The alkali metal polyacrylate includes at least one of sodium polyacrylate, lithium polyacrylate or potassium polyacrylate. The alkaline earth metal polyacrylate includes at least one of calcium polyacrylate or magnesium polyacrylate. By regulating the type of the first binder within the scope of the present application, the first binder can have good hydrophilicity, improve the lithium ion and electron transport capacity of the first binder, and have good tensile strength and the number of polar functional groups, improve the interfacial bonding force, and improve the nail penetration safety performance of the electrochemical device while taking into account good low-temperature discharge performance and cycle performance.
[0013] In one embodiment of the present application, the infrared spectrum of the first coating is at 3200 cm -1 Up to 3400cm -1 There is a characteristic peak between the first coating layer and the positive electrode current collector. When the infrared spectrum of the first coating layer has the characteristic peak, the hydroxyl functional group on the surface of the solid electrolyte can improve the affinity with the first binder, increase the cohesion of the first coating layer, and increase the bonding force between the first coating layer and the positive electrode current collector, thereby improving the nail penetration safety performance of the electrochemical device.
[0014] The second aspect of the present application provides an electronic device, which includes the electrochemical device in any of the aforementioned embodiments. Therefore, the electronic device provided by the present application can improve the nail penetration safety performance of the electrochemical device while taking into account good low-temperature discharge performance and cycle performance.
[0015] Beneficial effects of this application:
[0016] The first aspect of the present application provides an electrochemical device, the electrochemical device includes a positive electrode plate, the positive electrode plate includes a positive current collector, a first coating and a positive electrode material layer, the first coating is arranged on the surface of the positive current collector, the positive electrode material layer is arranged on the surface of the first coating away from the positive current collector, the first coating includes a first main material and a first binder, the first main material includes a solid electrolyte, the surface of the solid electrolyte is provided with a carbon material, and the Dv50 of the first main material is 50nm to 200nm. The thickness of the first coating is 0.5μm to 2μm. By regulating the type and thickness of the first coating and the Dv50 of the first main material within the scope of the present application, a first coating that is relatively dense, has high mechanical strength and good conductivity can be formed on the surface of the positive current collector, while improving the nail penetration safety performance of the electrochemical device while taking into account good low-temperature discharge performance and cycle performance.
[0017] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0019] Figure 1 A schematic diagram of the positive electrode structure of an embodiment of the present application;
[0020] Figure 2 This is an infrared spectrum test chart of the first coating layer of Example 1;
[0021] Figure 3 This is the infrared spectrum test chart of the first coating in Example 22.
[0022] Reference numerals:
[0023] 11-positive electrode current collector; 12-first coating layer; 13-positive electrode material layer. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present application and the accompanying drawings to clearly and completely describe the technical solutions in the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0025] It should be noted that in the specific embodiments of the present application, a lithium-ion battery is used as an example of an electrochemical device to explain the present application, but the electrochemical device of the present application is not limited to a lithium-ion battery.
[0026] The present application provides an electrochemical device, which includes a positive electrode plate, the positive electrode plate includes a positive electrode collector, a first coating and a positive electrode material layer, the first coating is arranged on the surface of the positive electrode collector, the positive electrode material layer is arranged on the surface of the first coating away from the positive electrode collector, the first coating includes a first main material and a first binder, the first main material includes a solid electrolyte, and a carbon material is arranged on the surface of the solid electrolyte. The Dv50 of the first main material is 50nm to 200nm, preferably Dv50 is 100nm to 150nm. Exemplarily, the value of Dv50 can be 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm or a range consisting of any two of the above values. The thickness of the first coating is 0.5μm to 2μm. Preferably, the thickness of the first coating is 0.5μm to 1μm. Exemplarily, the thickness of the first coating can be 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2.0μm or a range consisting of any two of the above values.
[0027] The inventors have found that by providing a first coating between the positive electrode current collector and the positive electrode material layer, the contact between the positive electrode material layer and the positive electrode current collector can be improved, and the low-temperature discharge performance and cycle performance can be improved. At the same time, the first coating provided also serves as a safety layer, which can improve the nail penetration safety performance of the electrochemical device. The first coating includes a first main material and a first binder, and the first main material includes a solid electrolyte, and a carbon material is provided on the surface of the solid electrolyte. The first main material uses a solid electrolyte, which can enhance the transmission capacity of lithium ions and electrons between the positive electrode material layer and the positive electrode current collector, and improve the low-temperature discharge performance of the electrochemical device. At the same time, the carbon material is provided on the surface of the main material, which can further improve the electron transmission capacity of the functional coating, increase the conductive channel of the electrochemical device during the cycle, and thus improve the cycle performance of the electrochemical device. Reducing the particle size Dv50 of the first main material to the nanometer level can increase the packing density between the first main materials, form a denser first coating on the surface of the positive electrode current collector, enhance the protection of the positive electrode current collector during the nail penetration test, wrap the metal burrs that may be generated by the positive electrode current collector during the nail penetration test, reduce the occurrence of short circuits in the electrochemical device, reduce the probability of thermal runaway caused by local overheating of the electrochemical device, and improve the nail penetration safety performance of the electrochemical device. When the Dv50 of the first main material is greater than 200nm, the first main material particles with too large a particle size are easy to puncture the positive electrode current collector during the nail penetration test, and the protection effect on the positive electrode current collector is poor; when the Dv50 of the first main material is less than 50nm, the process is more difficult, the production cost is higher, and the positive electrode plate has more side reactions with the electrolyte, resulting in a decrease in the cycle performance of the electrochemical device. When the thickness of the first coating is within the scope of this application, the first coating has high mechanical strength, can protect the positive electrode current collector during the nail penetration test, reduce the occurrence of short circuits in the electrochemical device, reduce the probability of thermal runaway caused by local overheating of the electrochemical device, and improve the nail penetration safety performance of the electrochemical device. When the thickness of the first coating is less than 0.5μm, the nail penetration safety performance of the electrochemical device is low. When the thickness of the first coating is greater than 2μm, the volume energy density of the electrochemical device is low, resulting in a decrease in the cycle performance of the electrochemical device. By regulating the type and thickness of the first coating and the Dv50 of the first main material within the scope of this application, a relatively dense first coating with high mechanical strength and good conductivity can be formed on the surface of the positive electrode current collector, while improving the nail penetration safety performance of the electrochemical device while taking into account good low-temperature discharge performance and cycle performance.
[0028] In this application, the above-mentioned “the first coating is disposed on the surface of the positive electrode current collector” means that the first coating can be disposed on one surface of the positive electrode current collector along its own thickness direction, or on two surfaces of the positive electrode current collector along its own thickness direction. It should be noted that the “surface” here can be the entire area of the positive electrode current collector, or it can be a partial area of the positive electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved. Specifically, if Figure 1 As shown, a first coating layer 12 and a positive electrode material layer 13 are sequentially stacked on the two surfaces of the positive electrode current collector 11. The above-mentioned "the positive electrode material layer is arranged on the surface of the first coating layer away from the positive electrode current collector" can be understood by analogy.
[0029] In the present application, Dv50 means a particle size at which the volume accumulation is 50% from the smaller particle size side in the volume-based particle size distribution of the first main material.
[0030] In one embodiment of the present application, the ratio of the thickness of the positive electrode material layer to the thickness of the first coating layer is 35 to 180. For example, the ratio of the thickness of the positive electrode material layer to the thickness of the first coating layer can be 35, 50, 70, 100, 150, 180, or a range consisting of any two of the above values. By adjusting the ratio of the thickness of the positive electrode material layer to the thickness of the first coating layer within the scope of the present application, the thickness of the positive electrode material layer and the first coating layer can be optimized, while improving the nail penetration safety performance of the electrochemical device while taking into account good low-temperature discharge performance and cycle performance.
[0031] In one embodiment of the present application, the thickness of the positive electrode material layer is 70 μm to 90 μm. For example, the thickness of the positive electrode material layer may be 70 μm, 80 μm, 90 μm or a range consisting of any two of the above values.
[0032] In one embodiment of the present application, the solid electrolyte includes lithium lanthanum zirconium oxide (Li 7 La 3 Zr 2 O 12 )、Lithium lanthanum titanium oxide(Li 3x La 2 / 3-x TiO 3 , wherein 0<x<0.16) or at least one of lithium aluminum titanium phosphate. Among them, lithium lanthanum titanium oxide may include but is not limited to Li 0.33 La 0.56 TiO 3 ; Lithium aluminum titanium phosphate may include but is not limited to lithium aluminum titanium phosphate Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3. Based on the mass of the first coating, the mass percentage of the first main material is 80% to 90%. Exemplarily, the mass percentage of the first main material can be 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90% or a range consisting of any two of the above values. By regulating the mass percentage of the first main material and the type of solid electrolyte within the scope of this application, the electronic conductivity of the first main material can be improved, and the transmission capacity of lithium ions and electrons can be improved, thereby improving the low-temperature discharge performance and cycle performance of the electrochemical device.
[0033] In one embodiment of the present application, the carbon material includes at least one of amorphous carbon, carbon nanotubes, conductive graphite or carbon nanofibers. Carbon nanotubes may include but are not limited to at least one of single-walled carbon nanotubes or multi-walled carbon nanotubes. Based on the mass of the first main material, the mass percentage of the carbon material is 3% to 5%. Exemplarily, the mass percentage of the carbon material can be 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%, 4.2%, 4.4%, 4.6%, 4.8%, 5.0% or a range consisting of any two of the above values. By regulating the type and mass percentage of the carbon material within the scope of the present application, a suitable carbon material can be arranged on the surface of the solid electrolyte, further improving the lithium ion and electron transport capacity of the first coating, thereby improving the low temperature discharge performance and cycle performance of the electrochemical device.
[0034] The present application has no particular restrictions on the preparation method of the solid electrolyte, as long as the purpose of the present application can be achieved. Exemplarily, the preparation method of the solid electrolyte may include but is not limited to the following steps: dispersing lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide or lithium aluminum titanium phosphate powder in an ethanol solution containing a silane coupling agent to obtain a suspension, heating the suspension at 25°C to 100°C for 1 to 6 hours, filtering the product, washing it with deionized water and ethanol multiple times, and then drying it in a drying oven at 70°C to 90°C for 10 to 12 hours to obtain a solid electrolyte containing hydroxyl functional groups on the surface. Among them, the silane coupling agent may include but is not limited to at least one of 3-aminopropyltriethoxysilane (APTES) or 3-glycidyloxypropyltrimethoxysilane (GPTS); the mass ratio of lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide or lithium aluminum titanium phosphate and the silane coupling agent is 99:1 to 90:10.
[0035] The present application has no particular restrictions on the preparation method of the first main material, as long as the purpose of the present application can be achieved. Exemplarily, the preparation method of the first main material may include but is not limited to the following steps: mixing the solid electrolyte and the carbon source in a mass ratio of 85:2 to 85:4, adding water, stirring and dispersing evenly to obtain a mixed solution, evaporating the mixed solution at 80°C to 120°C to remove the solvent, heat treating it in a nitrogen atmosphere at 500°C to 700°C for 7h to 9h, and grinding it after cooling to obtain the first main material. Among them, when the carbon material set on the surface of the solid electrolyte is any one of carbon nanotubes, conductive graphite or carbon nanofibers, the above carbon material can be directly added as a carbon source; when the carbon material set on the surface of the solid electrolyte is amorphous carbon, the above carbon source can be conductive carbon black or an organic carbon compound. Exemplarily, the organic carbon compound can include but is not limited to at least one of citric acid, glucose, sucrose or polyacrylic acid, and the organic carbon compound obtains amorphous carbon after the above heat treatment.
[0036] The present application does not particularly limit the method for regulating the mass percentage of the carbon material based on the first main material. For example, the mass percentage of the carbon material based on the first main material can be regulated by regulating the mass ratio of the solid electrolyte and the carbon material. When the mass ratio of the solid electrolyte and the carbon material decreases, the mass percentage of the carbon material based on the first main material increases; when the mass ratio of the solid electrolyte and the carbon material increases, the mass percentage of the carbon material based on the first main material decreases.
[0037] The present application has no particular restrictions on the method for regulating the Dv50 of the first main material. For example, the Dv50 of the first main material can be regulated by regulating the grinding time. When the regulated grinding time is reduced, the Dv50 of the first main material increases; when the regulated grinding time is increased, the Dv50 of the first main material decreases.
[0038] The present application does not particularly limit the method for regulating the resistivity of the first main material powder. For example, the resistivity of the first main material powder can be regulated by regulating the mass ratio of the solid electrolyte and the carbon material. When the mass ratio of the solid electrolyte and the carbon material decreases, the resistivity of the first main material powder increases; when the mass ratio of the solid electrolyte and the carbon material increases, the resistivity of the first main material powder decreases.
[0039] In one embodiment of the present application, the powder resistivity of the first main material is 50Ω·cm to 100Ω·cm. For example, the powder resistivity of the first main material can be 50Ω·cm, 55Ω·cm, 60Ω·cm, 65Ω·cm, 70Ω·cm, 75Ω·cm, 80Ω·cm, 85Ω·cm, 90Ω·cm, 95Ω·cm, 100Ω·cm, or a range consisting of any two of the above values. By regulating the powder resistivity of the first main material within the scope of the present application, the first main material can have a suitable powder resistivity, improve the lithium ion and electron transport capacity of the first main material, and thus improve the low-temperature discharge performance and cycle performance of the electrochemical device.
[0040] In one embodiment of the present application, the first binder includes a water-soluble metal salt compound, and the mass percentage of the first binder is 10% to 20% based on the mass of the first coating. Exemplarily, the mass percentage of the first binder can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, or a range consisting of any two of the above values. By regulating the mass percentage of the first binder within the scope of the present application, the first binder can interact well with the positive electrode sheet and enhance the interfacial bonding force, thereby enhancing the nail penetration safety performance of the electrochemical device while taking into account good low-temperature discharge performance and cycle performance.
[0041] In one embodiment of the present application, the first binder includes a water-soluble metal salt compound, and the water-soluble metal salt compound includes an alkali metal polyacrylate and / or an alkaline earth metal polyacrylate. The alkali metal polyacrylate includes at least one of sodium polyacrylate, lithium polyacrylate or potassium polyacrylate. The alkaline earth metal polyacrylate includes at least one of calcium polyacrylate or magnesium polyacrylate. By regulating the type of the first binder within the scope of the present application, the first binder can have good hydrophilicity, improve the lithium ion and electron transport capacity of the first binder, and have good tensile strength and the number of polar functional groups, thereby improving the interfacial bonding force, thereby improving the nail penetration safety performance of the electrochemical device while taking into account good low-temperature discharge performance and cycle performance.
[0042] In one embodiment of the present application, the infrared spectrum of the first coating is at 3200 cm -1 Up to 3400cm -1 There is a characteristic peak between them. When the infrared spectrum of the first coating has this characteristic peak, it means that the surface of the solid electrolyte has a hydroxyl functional group, which can form a hydrogen bond or a covalent bond with the carboxyl group in the first binder, thereby improving the affinity with the first binder, increasing the cohesion of the first coating, and increasing the bonding force between the first coating and the positive electrode current collector, thereby improving the nail penetration safety performance of the electrochemical device.
[0043] The present application has no particular restrictions on the preparation method of the positive electrode sheet, as long as the purpose of the present application can be achieved. For example, the preparation method of the positive electrode sheet may include but is not limited to the following steps: the solid electrolyte and the first binder are mixed in a mass ratio of (80 to 90): (10 to 20), deionized water is added as a solvent, and stirred evenly to obtain a first coating slurry with a solid content of 70wt% to 80wt%; then the first coating slurry is coated on one surface of the positive electrode current collector of 5μm to 20μm, and the first coating layer with a thickness of 0.5μm to 2μm is obtained after baking at 90℃ to 180℃ for 1h to 3h. Then prepare the positive electrode material layer slurry, apply the positive electrode material layer slurry on the surface of the first coating layer, dry it, and obtain a positive electrode sheet with a single-sided coating of the first coating layer and the positive electrode material layer. Repeat the above steps on the other surface of the positive electrode current collector to obtain a positive electrode sheet with a double-sided coating of the first coating layer and the positive electrode material layer.
[0044] When preparing the first coating, the first binder baked at 90°C to 180°C can increase the cohesion of the first coating and the bonding between the first coating and the positive electrode current collector. The reason is that, on the one hand, under the action of high temperature, the carboxyl group in the first binder (e.g., sodium polyacrylate) and the hydroxyl group in the solid electrolyte (e.g., lithium aluminum titanium phosphate) will undergo a dehydration reaction, and the water molecules generated during the reaction can promote the reaction between the first binder and the hydroxyl group on the surface of the solid electrolyte to form a stable chemical bond (e.g., ester bond); on the other hand, there is usually an oxide layer on the surface of the positive electrode current collector (e.g., there is an aluminum oxide layer for aluminum foil), and under the action of high temperature, the first binder (e.g., sodium polyacrylate) can react with the above oxide to generate a more stable compound, thereby increasing the cohesion of the first coating and the bonding between the first coating and the positive electrode current collector.
[0045] The present application has no particular limitation on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector).
[0046] The positive electrode material layer includes a positive electrode active material. The present application has no particular limitation on the positive electrode active material as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include but is not limited to lithium nickel cobalt manganese oxide (such as NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO 2 ), at least one of lithium manganese oxide, lithium iron manganese phosphate or lithium titanate.
[0047] The positive electrode material layer may also include a conductive agent and a second binder. The present application does not particularly limit the types of the conductive agent and the second binder, as long as the purpose of the present application can be achieved. For example, the conductive agent may include but is not limited to at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers, and the conductive carbon black may include but is not limited to at least one of acetylene black or Ketjen black. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers. Specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymers may include but are not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. For example, the second binder may include, but is not limited to, at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyimide, polyamide-imide, styrene-butadiene rubber, or polyvinylidene fluoride. The present application does not particularly limit the mass ratio of the positive electrode active material, the conductive agent, and the second binder in the positive electrode material layer, and those skilled in the art can select according to actual needs, as long as the purpose of the present application can be achieved.
[0048] The present application has no particular limitation on the thickness of the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector is 5 μm to 10 μm.
[0049] In the present application, the electrochemical device also includes a negative electrode plate, and the negative electrode plate includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The above-mentioned "negative electrode plate includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its own thickness direction, or can be disposed on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the surface of the negative electrode current collector, or it can be a partial area of the surface of the negative electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved.
[0050] The present application has no particular limitation on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a composite current collector. For example, the composite current collector may be a lithium-copper composite current collector, a carbon-copper composite current collector, a nickel-copper composite current collector or a titanium-copper composite current collector, etc.
[0051] The negative electrode material layer includes a negative electrode active material. The present application has no particular limitation on the negative electrode active material as long as the purpose of the present application can be achieved. For example, the negative electrode active material may include but is not limited to natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO 2 , spinel-structured lithiated TiO 2 -Li 4 Ti 5 O 12 Or at least one of Li-Al alloy.
[0052] In some embodiments of the present application, the negative electrode material layer may further include a conductive agent and a second binder, for example, at least one of the conductive agent and the second binder. The present application does not particularly limit the mass ratio of the negative electrode active material, the conductive agent, and the second binder in the negative electrode material layer, and those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.
[0053] The present application has no particular limitation on the thickness of the negative electrode material layer and the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode material layer is 80 μm to 100 μm, and the thickness of the negative electrode current collector is 4 μm to 15 μm.
[0054] Optionally, the negative electrode plate may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art. For example, the conductive layer includes a conductive agent and a second binder. The present application has no particular restrictions on the conductive agent and the second binder in the conductive layer, which may be, for example, at least one of the above conductive agent and the above second binder.
[0055] In the present application, the electrochemical device also includes an isolation membrane. The present application has no particular restrictions on the isolation membrane, as long as the purpose of the present application can be achieved. For example, the material of the isolation membrane may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (e.g., polyethylene terephthalate (PET) membranes), cellulose, polyimide (PI), polyamide (PA), spandex or aramid. The type of isolation membrane may include at least one of a woven membrane, a non-woven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.
[0056] In some embodiments of the present application, the isolation film may include a substrate layer and a surface treatment layer. The substrate layer may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used.
[0057] Optionally, a surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.
[0058] In some embodiments of the present application, the inorganic layer includes ceramic particles and a second binder. The present application has no particular restrictions on ceramic particles, such as ceramic particles may include at least one of silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the second binder, such as the second binder may be at least one of the above-mentioned second binders. In some embodiments of the present application, the polymer layer includes a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly (vinylidene fluoride-hexafluoropropylene).
[0059] In the present application, there is no particular limitation on the thickness of the isolation film, as long as the purpose of the present application can be achieved. For example, the thickness of the isolation film may be 3 μm to 30 μm.
[0060] In the present application, the electrochemical device further includes an electrolyte, and the electrolyte includes a lithium salt and a non-aqueous solvent.
[0061] The present application has no particular restrictions on lithium salts, as long as the purpose of the present application can be achieved. For example, lithium salts may include but are not limited to LiPF 6 , LiBF 4 、LiAsF 6 、LiClO 4 、LiB(C 6 H 5 ) 4 、LiCH 3 SO 3 、LiCF 3 SO 3 、LiN(SO 2 CF 3 ) 2 、LiC(SO 2 CF 3 )3 , Li 2 SiF 6 At least one of lithium bis(oxalato)borate (LiBOB) or lithium difluoroborate. The present application has no particular limitation on the content of lithium salt in the electrolyte, as long as the purpose of the present application can be achieved.
[0062] The present application has no particular limitation on the non-aqueous solvent as long as the purpose of the present application can be achieved. For example, the non-aqueous solvent may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents.
[0063] The carbonate compound may include but is not limited to at least one of a chain carbonate compound, a cyclic carbonate compound or a fluorinated carbonate compound. The chain carbonate compound may include but is not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or ethyl methyl carbonate (MEC). The cyclic carbonate compound may include but is not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The fluorinated carbonate compound may include, but is not limited to, at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include, but is not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate. The present application has no particular restrictions on the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved.
[0064] The electrochemical device also includes a housing for accommodating a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, as well as other components known in the field of electrochemical devices, and this application does not limit the above-mentioned other components. This application does not particularly limit the housing, and it can be a housing known in the art, as long as the purpose of this application can be achieved. For example, the housing can be a hard shell housing or a flexible shell. The material of the hard shell housing can be metal, and this application does not limit the type of metal, and a metal hard shell housing known in the art can be used, as long as the purpose of this application can be achieved. The flexible housing can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.
[0065] The preparation process of the electrochemical device of the present application is well known to those skilled in the art, and the present application has no particular limitations. For example, the preparation process of the electrochemical device may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly with a wound structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain an electrochemical device. Alternatively, stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly with a stacked structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain an electrochemical device. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the shell as needed to prevent pressure rise and overcharge and discharge inside the electrochemical device.
[0066] The second aspect of the present application provides an electronic device, which includes the electrochemical device in any of the aforementioned embodiments. Therefore, the electronic device provided by the present application has good nail penetration safety performance, low-temperature discharge performance and cycle performance.
[0067] The electronic device of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0068] Example
[0069] Hereinafter, the embodiments of the present application will be described in more detail with reference to Examples and Comparative Examples. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are by mass.
[0070] Test methods and equipment:
[0071] First coating thickness test
[0072] The positive electrode sheet was plasma cut longitudinally along the thickness direction and polished by argon ion polishing technology to obtain a flat cross section. Then, a scanning electron microscope (OXFORD·EDS) was used with a magnification of 40,000 times to observe and measure the thickness of the first coating at three locations. The average value was taken as the thickness of the first coating.
[0073] Particle size testing
[0074] The particle size of the first main material was measured using a Malvern particle size tester (model: MasterSizer 2000). 0.02 g of the first main material was added to a 50 mL clean beaker, and 20 mL of dispersant ethanol was added. The first main material was completely dispersed in ethanol by ultrasonic cleaning in a 120 W ultrasonic cleaning machine for 30 minutes to obtain a sample dispersion. The sample dispersion was tested using a Malvern particle size tester to obtain the particle size Dv50 of the first main material.
[0075] Nail penetration test
[0076] Take 10 lithium-ion batteries in the embodiment, charge the lithium-ion batteries to 4.5V at a constant current of 0.5C under an environment of 25±3°C, and charge them at a constant voltage until the current is cut off at 0.05C to obtain a lithium-ion battery in a fully charged state, and then use a steel nail with a diameter of 4mm, made of carbon steel, with a taper of 16.5mm, and a total length of 100mm to perform a nail penetration test on the fully charged lithium-ion battery under an environment of 25±3°C. The nail penetration speed is set to 30mm / s, and the nail penetration depth is based on the taper of the steel nail passing through the lithium-ion battery. Observe the state of the lithium-ion battery during the test, and take the lithium-ion battery as the criterion for not burning or exploding as the judgment standard, record it as passing the nail penetration test, and record the number of lithium-ion batteries that pass the nail penetration test. The safety performance of the lithium-ion battery is characterized by the nail penetration test pass rate. The higher the nail penetration test pass rate, the better the safety performance of the lithium-ion battery. Nail penetration test pass rate = number of lithium-ion batteries that pass the nail penetration test / 10.
[0077] Cyclic performance test
[0078] After the lithium-ion battery is left to stand for 30 minutes in an environment of 45℃±3℃, it is charged to 4.25V at a constant current of 1.25C, then charged to 4.5V at a constant current of 1.5C, then charged to 0.05C at a constant voltage of 4.5V, left to stand for 30 minutes, and then discharged to 3.0V at a constant current of 0.7C. The discharge capacity obtained in this step is the initial capacity. Repeat the above cycle, and the discharge capacity of each step is compared with the initial capacity to obtain the discharge capacity retention rate of each step, and record the number of cycles of the lithium-ion battery at 45℃±3℃ until the discharge capacity retention rate is 80%. The number of cycles at 45℃±3℃ until the capacity retention rate is 80% is recorded as the cycle performance of the lithium-ion battery. The higher the number of cycles of the lithium-ion battery at 45℃±3℃ until the capacity retention rate is 80%, the better the cycle performance of the lithium-ion battery.
[0079] Low temperature discharge performance test
[0080] After the lithium-ion battery was left at rest for 5 minutes at 25℃±3℃, it was charged to 4.5V at 1.5C constant current and charged to 0.02C current cutoff at constant voltage; at the same 25℃±3℃ environment, it was discharged to 3.0V at 0.2C constant current. The initial discharge capacity at 3.0V was recorded.
[0081] After the lithium-ion battery is left at 25℃±3℃ for 5 minutes, it is charged to 4.5V at 1.5C constant current and charged to 0.02C current cutoff at constant voltage; the furnace temperature is adjusted to -10℃; the lithium-ion battery is left for 60 minutes; and discharged to 3.0V at 0.2C constant current. The low-temperature discharge capacity when discharged to 3.0V is recorded. The higher the low-temperature discharge capacity retention rate of the lithium-ion battery at -10℃, the better the low-temperature discharge performance of the lithium-ion battery.
[0082] -10℃ low temperature discharge capacity retention rate = (low temperature discharge capacity / initial discharge capacity) × 100%.
[0083] Powder resistivity test
[0084] After the lithium-ion battery is discharged to 3V at 0.2C, the positive electrode sheet is removed, and the positive electrode material layer is scraped off with a knife. Then, the first coating is scraped off from the positive electrode current collector to obtain a first coating powder. The first coating powder is heated at 400°C in air to obtain a first main material. The powder resistivity of the first main material is tested with a powder resistivity meter in a drying room to obtain the powder resistivity ρ of the first main material.
[0085] Infrared spectrum test
[0086] The lithium-ion battery was discharged at a constant current of 0.1C to 3.0V, and the lithium-ion battery was disassembled to obtain the positive electrode sheet, which was cleaned with dimethyl carbonate (DMC) for 10 minutes, and then baked at 100°C for 2 hours for standby use. The positive electrode material layer on the positive electrode sheet was scraped off to obtain a positive current collector with a first coating on the surface.
[0087] The infrared spectrum of the positive electrode current collector coated with the first coating was tested by an infrared spectrometer (model: Nicolet iS50) using a potassium bromide (KBr) tablet method. Figure 2 This is the infrared spectrum test chart of the first coating of Example 1, Figure 3 This is the infrared spectrum test chart of the first coating in Example 22.
[0088] Carbon material content test
[0089] The lithium-ion battery was discharged at a constant current of 0.2C to 3V, and the lithium-ion battery was disassembled to obtain the positive electrode sheet, and the positive electrode material layer on the positive electrode sheet was scraped off to obtain the positive electrode current collector with the first coating on the surface. The positive electrode current collector was cut into 10 samples of 48mm×60mm, and the samples were heated at 400°C in air. After cleaning and drying, the carbon content in the 10 samples was tested using an inductively coupled plasma analyzer (ICP, model AVIO-200), and the average value was taken to obtain the content of carbon material in the first main material.
[0090] Example 1
[0091] <Preparation of solid electrolyte>
[0092] Lithium aluminum titanium phosphate powder is dispersed in an ethanol solution containing 3-aminopropyltriethoxysilane, the mass ratio of lithium aluminum titanium phosphate to 3-aminopropyltriethoxysilane is 95:5, to obtain a suspension. After the suspension is heated at 75°C for 4 hours, the product is filtered, washed with deionized water and ethanol several times, and then dried in a drying oven at 80°C for 12 hours to obtain a solid electrolyte containing hydroxyl functional groups on the surface.
[0093] <Preparation of the first main material>
[0094] The solid electrolyte prepared above and citric acid were mixed in a mass ratio of 85:3, and then water was added. After stirring and dispersing evenly, a mixed solution was obtained. After the mixed solution was evaporated and dried at 100°C to remove the solvent, it was heat treated at 600°C in a nitrogen atmosphere for 8 hours, and then ground after cooling to obtain the first main material. Among them, citric acid obtained amorphous carbon after the above heat treatment; the Dv50 of the first main material was 150nm, the powder resistivity ρ of the first main material was 50.02Ω·cm, and the mass percentage of carbon material based on the first main material W C It is 4%.
[0095] <Preparation of positive electrode sheet>
[0096] The first main material prepared above and the first binder sodium polyacrylate were mixed in a mass ratio of 85:15, deionized water was added as a solvent, and the mixture was stirred evenly to obtain a first coating slurry with a solid content of 75wt%, which was coated on one surface of a 10μm positive electrode current collector aluminum foil, and the first coating was obtained after baking at 120°C for 2 hours. The positive electrode active material lithium cobalt oxide, the second binder polyvinylidene fluoride and the conductive agent conductive carbon black were mixed in a mass ratio of 97.3:1.6:1.1, N-methylpyrrolidone (NMP) was added as a solvent, and the mixture was stirred evenly in a vacuum mixer to obtain a positive electrode slurry with a solid content of 75wt%. The positive electrode slurry was evenly coated on the surface of the first coating, and dried at 120°C to obtain a positive electrode sheet with a single-sided coating of the first coating and the positive electrode material layer. The coating weight of the positive electrode active layer was 267.8mg / 1540mm 2 Then repeat the above steps on the other surface of the aluminum foil, and after drying at 120°C, a positive electrode sheet with a first coating layer and a positive electrode material layer on both sides is obtained. Then, after cold pressing, cutting, and welding the tabs, a positive electrode sheet with a specification of 74mm×867mm is obtained for standby use. Among them, based on the mass of the first coating layer, the mass percentage of the first main material W 1 The mass percentage of the first binder is 85%. 2 is 15%; the thickness of the first coating D 1 The thickness of the single-sided positive electrode material layer is 1 μm. 2 is 85 μm, and the ratio of the thickness of the positive electrode material layer to the thickness of the first coating layer is D 2 / D 1 is 85.
[0097] The schematic diagram of the structure of the positive electrode sheet prepared in Example 1 is as follows Figure 1 shown.
[0098] <Preparation of negative electrode sheet>
[0099] The negative electrode active material artificial graphite, the second binder styrene butadiene rubber (SBR) and the second binder carboxymethyl cellulose (CMC) were mixed at a mass ratio of 97.7:1:1.3, and then deionized water was added as a solvent to prepare a slurry with a solid content of 70wt%. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 6μm, and dried at 120°C to obtain a negative electrode sheet with a single-sided negative electrode material layer. The coating weight of the negative electrode material layer was 142mg / 1540mm 2Then repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet with a negative electrode material layer coated on both sides. After drying at 120°C, cold pressing, cutting and welding the tabs, a negative electrode sheet with a specification of 78mm×875mm is obtained for standby use. The thickness of the single-sided negative electrode material layer is 80μm.
[0100] <Preparation of Electrolyte>
[0101] In an argon atmosphere glove box with a water content of less than 10 ppm, carbonate compounds ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) were uniformly mixed in a mass ratio of 10:30:60 to obtain a base solvent, and lithium salt LiPF 6 Stir evenly to obtain an electrolyte. Based on the total mass of the electrolyte, the lithium salt LiPF 6 The mass percentage is 12.5%, and the balance is the basic solvent.
[0102] <Isolation film>
[0103] A polyethylene porous polymer film with a thickness of 8 μm (manufacturer: Celgard Membrane Co., Ltd., USA) was used as a separator.
[0104] <Preparation of lithium-ion batteries>
[0105] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, with the separator placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain an electrode assembly, which is then packed into an aluminum-plastic film packaging bag, dehydrated at 80°C, and injected with the prepared electrolyte. After vacuum packaging, standing, forming, and shaping processes, a lithium-ion battery is obtained.
[0106] The upper limit voltage of the formation is 4.53V, the formation temperature is 85℃, and the formation time is 50min.
[0107] Example 2
[0108] Except that <Preparation of solid electrolyte> is replaced by the following steps, the rest is the same as Example 1.
[0109] <Preparation of solid electrolyte>
[0110] Lithium lanthanum zirconium oxide powder is dispersed in an ethanol solution containing 3-aminopropyltriethoxysilane to obtain a suspension. After the suspension is heated at 75°C for 4 hours, the product is filtered, washed with deionized water and ethanol several times, and then dried in a drying oven at 80°C for 12 hours to obtain a solid electrolyte containing hydroxyl functional groups on the surface.
[0111] Example 3
[0112] Except that <Preparation of solid electrolyte> is replaced by the following steps, the rest is the same as Example 1.
[0113] <Preparation of solid electrolyte>
[0114] Lithium lanthanum titanium oxide Li 0.33 La 0.56 TiO 3 The powder is dispersed in an ethanol solution containing 3-aminopropyltriethoxysilane to obtain a suspension. After the suspension is heated at 75°C for 4 hours, the product is filtered, washed with deionized water and ethanol multiple times, and then dried in a drying oven at 80°C for 12 hours to obtain a solid electrolyte containing hydroxyl functional groups on the surface.
[0115] Embodiment 4 to Embodiment 7
[0116] In addition to adjusting the mass ratio of the first main material and the first binder in the preparation of the positive electrode sheet, the mass percentage content of the first main material based on the first coating is W 1 and the mass percentage content W of the first binder based on the first coating 2 Except as shown in Table 1, the rest is the same as Example 1.
[0117] Example 8 to Example 10
[0118] Except that the grinding time is adjusted in <Preparation of the first main material> so that the Dv50 of the first main material is as shown in Table 1, the rest is the same as Example 1.
[0119] Example 11 to Example 13
[0120] In addition to adjusting the thickness D of the first coating according to Table 1 1 , the ratio of the thickness of the positive electrode material layer to the thickness of the first coating layer D 2 / D 1 As a result, the thickness of the positive electrode material layer D 2 Except for the above, the rest is the same as Example 1.
[0121] Example 14 to Example 15
[0122] Except for adjusting the type of carbon material according to Table 1, the rest is the same as Example 1.
[0123] Example 16 to Example 19
[0124] In addition to adjusting the mass ratio of the solid electrolyte and citric acid in the preparation of the first main material, the carbon material is based on the mass percentage content W of the first main material. C As shown in Table 1, except that the powder resistivity of the first main material is changed accordingly, the rest is the same as in Example 1.
[0125] Example 20 to Example 21
[0126] Except for adjusting the type of the first adhesive according to Table 1, the rest is the same as Example 1.
[0127] Embodiment 22
[0128] The process is the same as that of Example 1 except that the untreated lithium aluminum titanium phosphate in the <Preparation of solid electrolyte> of Example 1 is directly used as the solid electrolyte in <Preparation of first main material>.
[0129] Comparative Example 1
[0130] Except that the first coating layer is not provided on the surface of the positive electrode current collector, the rest is the same as that of Example 1.
[0131] Comparative Example 2
[0132] The above method is the same as Example 1 except that in <Preparation of the First Main Material>, no carbon material is provided on the surface of the solid electrolyte and the solid electrolyte is directly used as the first main material.
[0133] Comparative Examples 3 to 6
[0134] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1.
[0135] The preparation parameters and performance tests of various embodiments and comparative examples are shown in Table 1.
[0136] Table 1
[0137] Note: “ / ” in Table 1 means that there is no corresponding preparation parameter or substance. C Indicates the mass percentage of carbon material based on the first main material, W 1 Indicates the mass percentage of the first main material based on the first coating, W 2 It represents the mass percentage of the first binder based on the first coating, D 1 Indicates the thickness of the first coating, D 2 represents the thickness of the single-sided positive electrode material layer, ρ represents the powder resistivity of the first main material, and the characteristic peak refers to the infrared spectrum of the first coating at 3200cm -1 Up to 3400cm -1 The characteristic peaks between .
[0138] It can be seen from Examples 1 to 22 and Comparative Examples 1 to 6 that when a solid electrolyte having a carbon material on its surface is used as the first main material of the first coating, the positive electrode plate has the first coating structure of the present application, and the Dv50 of the first main material and the thickness of the first coating are within the range of the present application, the lithium-ion battery has a high -10°C low-temperature discharge capacity retention rate, 80% capacity retention cycles and nail penetration test pass rate. This indicates that the lithium-ion battery of the present application has high nail penetration safety performance while taking into account good low-temperature discharge performance and cycle performance.
[0139] The type of solid electrolyte and the type of the first binder usually affect the nail penetration safety performance, low temperature discharge performance and cycle performance of the lithium-ion battery. It can be seen from Examples 1 to 3 and Examples 20 to 21 that when the type of solid electrolyte and the type of the first binder are within the scope of this application, the -10°C low temperature discharge capacity retention rate, 80% capacity retention cycles and nail penetration test pass rate of the lithium-ion battery are high, which shows that the lithium-ion battery of this application has high nail penetration safety performance while taking into account good low temperature discharge performance and cycle performance.
[0140] The mass percentage W of the first main material based on the first coating 1 and the mass percentage content W of the first binder based on the first coating 2 It usually affects the nail penetration safety performance, low temperature discharge performance and cycle performance of lithium-ion batteries. It can be seen from Examples 1 and 4 to 7 that when W 1 and W 2 Within the scope of this application, the lithium-ion battery has a high -10°C low-temperature discharge capacity retention rate, 80% capacity retention cycles and nail penetration test pass rate, which means that the lithium-ion battery of this application has high nail penetration safety performance while taking into account good low-temperature discharge performance and cycle performance.
[0141] The ratio of the thickness of the positive electrode material layer to the thickness of the first coating layer D 1 / D 2 It usually affects the nail penetration safety performance, low temperature discharge performance and cycle performance of lithium-ion batteries. It can be seen from Examples 1 and 11 to 13 that when D 1 / D 2 Within the scope of this application, the lithium-ion battery has a high -10°C low-temperature discharge capacity retention rate, 80% capacity retention cycles and nail penetration test pass rate, which means that the lithium-ion battery of this application has high nail penetration safety performance while taking into account good low-temperature discharge performance and cycle performance.
[0142] Type of carbon material, mass percentage of carbon material based on the first main material W CThe powder resistivity of the first main material usually affects the nail penetration safety performance, low temperature discharge performance and cycle performance of the lithium ion battery. C When the powder resistivity of the first main material is within the scope of this application, the -10°C low-temperature discharge capacity retention rate, 80% capacity retention cycles and nail penetration test pass rate of the lithium-ion battery are high, which means that the lithium-ion battery of this application has high nail penetration safety performance while taking into account good low-temperature discharge performance and cycle performance.
[0143] The infrared spectrum of the first coating is at 3200 cm -1 Up to 3400cm -1 Whether there is a characteristic peak between the two usually affects the nail penetration safety performance, low temperature discharge performance and cycle performance of lithium-ion batteries. It can be seen from Examples 1 and 22 that the infrared spectrum of the first coating of Example 1 is at 3200cm -1 Up to 3400cm -1 There are characteristic peaks between them. The infrared spectrum of the first coating of Example 22 is at 3200cm -1 Up to 3400cm -1 There is no characteristic peak between 3200cm and 3200cm. The -10℃ low-temperature discharge capacity retention rate, 80% capacity retention cycles and nail penetration test pass rate of Example 1 are higher. -1 Up to 3400cm -1 The lithium-ion batteries with characteristic peaks have better nail penetration safety performance, low-temperature discharge performance and cycle performance, which means that the lithium-ion battery of the present application has high nail penetration safety performance while taking into account good low-temperature discharge performance and cycle performance.
[0144] Specifically, Figure 2 As shown, Figure 2 This is the infrared spectrum test chart of the first coating of Example 1. In the infrared spectrum test chart, 3200cm -1 Up to 3400cm -1 There are characteristic peaks between them, indicating that the solid electrolyte surface has hydroxyl functional groups; Figure 3 As shown, Figure 3 This is the infrared spectrum test chart of the first coating of Example 22. In the infrared spectrum test chart, 3200cm -1 Up to 3400cm -1 There is no characteristic peak between them, indicating that the solid electrolyte surface does not have hydroxyl functional groups.
[0145] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
[0146] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.
[0147] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
Claims
1. An electrochemical device, comprising a positive electrode plate, wherein the positive electrode plate comprises a positive electrode collector, a first coating and a positive electrode material layer, wherein the first coating is arranged on the surface of the positive electrode collector, and the positive electrode material layer is arranged on the surface of the first coating away from the positive electrode collector, the first coating comprises a first main material and a first binder, the first main material comprises a solid electrolyte, a carbon material is arranged on the surface of the solid electrolyte, the Dv50 of the first main material is 50nm to 200nm, and the thickness of the first coating is 0.5μm to 2μm.
2. The electrochemical device according to claim 1, wherein: The Dv50 of the first main material is 100nm to 150nm.
3. The electrochemical device according to claim 1, wherein The thickness of the first coating layer is 0.5 μm to 1 μm.
4. The electrochemical device according to claim 1, wherein The ratio of the thickness of the positive electrode material layer to the thickness of the first coating layer is 35 to 180.
5. The electrochemical device according to claim 1, wherein The solid electrolyte includes at least one of lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide or lithium aluminum titanium phosphate; based on the mass of the first coating, the mass percentage of the first main material is 80% to 90%.
6. The electrochemical device according to claim 1, wherein The carbon material includes at least one of amorphous carbon, carbon nanotubes, conductive graphite or carbon nanofibers; based on the mass of the first main material, the mass percentage of the carbon material is 3% to 5%.
7. The electrochemical device according to claim 1, wherein: The powder resistivity of the first main material is 50 Ω·cm to 100 Ω·cm.
8. The electrochemical device according to claim 1, wherein The first binder includes a water-soluble metal salt compound; based on the mass of the first coating, the mass percentage of the first binder is 10% to 20%.
9. The electrochemical device according to claim 8, wherein: The water-soluble metal salt compound includes alkali metal polyacrylate and / or alkaline earth metal polyacrylate; the alkali metal polyacrylate includes at least one of sodium polyacrylate, lithium polyacrylate or potassium polyacrylate; the alkaline earth metal polyacrylate includes at least one of calcium polyacrylate or magnesium polyacrylate.
10. The electrochemical device according to claim 1, wherein The infrared spectrum of the first coating is at 3200 cm -1 Up to 3400cm -1 There are characteristic peaks between them.
11. An electronic device comprising the electrochemical device according to any one of claims 1 to 10.
Citation Information
Patent Citations
Electrochemical device
CN111199833A
Electrochemical device and electronic device
CN117832589A
Positive pole piece, solid-state battery containing positive pole piece and preparation method of positive pole piece
CN118522979A
Electrode assembly, electrochemical device and electric device
WO2025001892A1